Calagem superficial até 12 t ha-1 em plantio direto : produtividade da soja e efeitos no solo - Aguiar, Beatriz Lima (2021)
The superficial application of lime is an alternative for maintaining and correcting the acidity of the soil under no-tillage already consolidated. When using the base saturation method for the determination of liming, it is observed that the values found after correction are lower than those determined in theory. Thus, this study worked with the hypotheses that the application of limestone with different doses and sources in a clayey soil in consolidated SPD, interferes in the chemical attributes of the soil in the superficial and subsurface layer over time, in the productivity of the soybean crop and that base saturation can reach values equal to or close to those determined in the liming requirement formula. The main objective was to evaluate the effects of surface and incorporated application of calcitic and dolomitic limestone in different doses and granulometries, determined from two different methods, on the chemical attributes of the soil and on the nutrition and productivity of the soybean crop. The experiment was conducted in the municipality of Sinop-MT, in an area under no-tillage system under soybean-corn cultivation annually. The treatments had doses varying from 2.5 to 12.3 tons / ha-1 with two types of limestone with different granulometries applied on the surface and incorporated. Soil chemical attributes were evaluated in the 0-5.0-10 and 0- 20 cm layers, and the soybean yield and nutrition components in two harvests. There was a decrease in potential acidity, increase in pH and Ca ratio: Mg in the 0-5 and 0-10 cm layer. In the 0-20 cm layer, the soil variables that showed statistical differences were: pH, Mg, Ca, H + Al, SB, V% and all the relationships between the bases. cm obtained the highest values of saturation per base. In the harvests, soybeans were influenced by the accumulated productivity of the two harvests and in the foliar proportions of P, K and Fe.